The lived experiences of a COVID-19 immunization programme: vaccine hesitancy and vaccine refusal - Nee Nee Chan; Khang Wei Ong; Ching Sin Siau; Kai Wei Lee; Suat Cheng Peh; Shakila Yacob; Yook Chin Chia; Vei Ken Seow; Pei Boon Ooi (BMC, 2022)
Abstract Background The COVID-19 pandemic has resulted in a global health emergency and lock-down measures to curb the uncontrolled transmission chain. Vaccination is an effective measure against COVID-19 infections. In Malaysia amidst the national immunisation programme (NIP) which started in February 2021, there were rising concerns regarding the prevalence of vaccine hesitancy and refusal, and therefore, vaccine uptake among Malaysians. Although there are many quantitative studies on COVID-19 vaccination, the subjective experience of individuals was understudied. This study aims to explore the lived experiences of Malaysians regarding vaccine hesitancy and refusal, and facilitating factors that could enhance vaccine acceptance and uptake. Methods This qualitative study employed the hermeneutic phenomenological study design. Purposive sampling strategies were used to recruit Malaysians that had direct experiences with friends, family members and their community who were hesitating or refusing to accept the COVID-19 vaccines. A semi-structured interview guide was developed based on the expert knowledge of the investigators and existing literature on the topic. A series of focus group interviews (FGIs) was conducted online facilitated by a multidisciplinary team of experts. The group interviews were transcribed verbatim and analysed. Results Fifty-nine participants took part in seven FGIs. We found that "incongruence" was the overall thematic meaning that connected all the 3 main themes. These themes comprise firstly, the incongruence between the aims and implementation of the National Immunization Program which highlighted the gap between realities and needs on the ground. Secondly, the incongruence between Trust and Mistrust revealed a trust deficit in the government, COVID-19 news, and younger people's preference to follow the examples of local vaccination "heroes". Thirdly, the incongruence in communication showed the populace's mixed views regarding official media and local social media. Conclusions This study provided rich details on the complex picture of the COVID-19 immunization program in Malaysia and its impact on vaccine hesitancy and refusal. The inter-related and incongruent factors explained the operational difficulty and complexity of the NIP and the design of an effective health communication campaign. Identified gaps such as logistical implementation and communication strategies should be noted by policymakers in implementing mitigation plans.